KARAKTERISTIK PERKEMBANGAN ANAK USIA DINI - Ulfiani Rahman (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
Early education plays an important role in developing potential human resources. Such education, therefore, should be developed for the future of a nation. To get a maximum outcome, the process of education should be well-planned and systemic, also, the need and the way of children learn should be a priority. This is one way of teachers to stimulate students’ interest and their curiousity by involving them totally in the learning process. This approach may lead students interact with their environment positively.